1992
DOI: 10.1177/019459989210700313
|View full text |Cite
|
Sign up to set email alerts
|

Surface Sensibility of the Floor of the Mouth and Tongue in Healthy Controls and in Radiated Patients

Abstract: Increased areas of anesthesia in the oral cavity have been shown to significantly impair oral function in normal individuals. In patients who undergo oral cavity reconstruction, loss of sensation plays a major role in producing disturbances in postoperative oral function. Free tissue transfer techniques have permitted the problem of sensory loss to be addressed through the use of sensate cutaneous free flaps, in which microneural anastomoses are performed between a sensory nerve supplying the flap and a recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 27 publications
(8 reference statements)
1
32
0
Order By: Relevance
“…Many authors have reported reduced, delayed or failed sensory recovery in radiated patients 1,4,15 . A tendency for better sensory recovery of the flaps is believed to occur in younger age patients 1,5,16 and in non-smokers 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported reduced, delayed or failed sensory recovery in radiated patients 1,4,15 . A tendency for better sensory recovery of the flaps is believed to occur in younger age patients 1,5,16 and in non-smokers 5 .…”
Section: Discussionmentioning
confidence: 99%
“…This variability is due to the individual variation in tongue volume, tongue sensation, and tongue mobility. Tongue volume, 19 sensation, 3,20 and mobility 3,21 have been considered important to masticatory function, yet a systematic investigation of head and neck cancer patients that specifically assesses tongue function Normals had significantly higher molar and incisal biting force than did both reconstructed and nonreconstructed patients (p < .001). Significant differences were seen between all three groups with regard to tongue function (p < .002).…”
Section: Discussionmentioning
confidence: 99%
“…Subtle age-related alterations in sensation and physiologic function have been reported in the absence of underlying disease processes [21]. For example, declines in sensation have been reported for vibratory, gustatory, and tactile stimuli at various sites in the oral cavity, such as the tongue, floor of the mouth, and hard palate [22][23][24][25][26][27][28][29], and in the laryngopharynx [5]. In contrast, age-stable responses have been demonstrated in response to thermal [23,29] and somatic stimulation of the oral cavity [23,25,30].…”
Section: Age-related Changes In Sensation and Swallowingmentioning
confidence: 99%
“…Diminution in sensitivity to vibrotactile stimulation of the lower lip and tongue has been demonstrated [23,24,28], and agerelated decrements in sensation have been reported for oral stereognosis tasks [23,29] and punctate pressure applications [29]. Using two-point discrimination tasks, sensitivity appears to be age-stable at anterior lingual sites [22,23,25] but prone to age-related change at distal lingual areas and the floor of the mouth [22]. Several studies have used air puffs as a somatic stimulus in sensitivity testing.…”
Section: Age-related Changes In Sensation and Swallowingmentioning
confidence: 99%